PENGENALAN PERMAINAN TRADISIONAL INDONESIA DI KELAS BIPA - Asteria, Prima Vidya (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
This study aimed to describe the introduction of Indonesian Traditional Games in Unesa BIPAâ€™s Class that includes planning, implementation, and evaluation. This study used descriptive qualitative method. This research was conducted in classes BIPA Unesa in the course Introduction to Indonesian Culture, February 17, 2016. The subjects were students who take the program BIPA Unesa Dharmasiswa class of 11 students . The stages of this study include the initial, core, end. In the early stage, researcher collecting information about situation in BIPA class at Unesa and creating syllabus and instruments. At the core stage, researcher doing learning and teaching process based on syllabus. At the last stage is evaluating of learning. Things that exist during the learning and teaching process that the students are very enthusiastic attention and focus on lecturer and model. Based on the task, students' ability is quite good with an average of 83.Â